Psychological characteristics of early stuttering. (2nd November 2021) - Park, Veronica; Onslow, Mark; Lowe, Robyn; Jones, Mark; O'Brian, Sue; Packman, Ann; Menzies, Ross G.; Block, Susan; Wilson, Linda; Harrison, Elisabeth; Hewat, Sally
Abstract: Purpose: The purpose of this study was to use psychological measures of pre-schoolers who stutter and their parents to inform causal theory development and influence clinical practices. This was done using data from a substantive clinical cohort of children who received early stuttering treatment. Method: The cohort ( N = 427) comprised parents and their children who were treated with the Lidcombe Program, the Westmead Program, and the Oakville Program. The study incorporated demographic information, stuttering severity, and child and parent psychological measures prior to treatment. Result: The cohort revealed nothing unusual about behavioural and emotional functioning, or the temperaments, of pre-school children that would influence treatment, be targeted during treatment, or influence causal theory development. However, a third of parents were experiencing moderate to high life stressors at the time of seeking treatment, and half the parents failed first-stage screening for Anankastic Personality Disorder. Conclusion: The present results are consistent with a number of previous reports that showed that the population of pre-schoolers who stutter have no unusual psychological profiles. Hence, these results suggest that the association between mental health and stuttering later in life is a consequence of the disorder rather than being a part of its cause. The finding of the life stress of parents who seek stuttering treatment for pre-school children has potential clinical importance and warrants further investigation. Further psychological research is required about parents of pre-school children who stutter, because half the parents in the cohort failed the screener for Anankastic Personality Disorder. This is of interest because a previous study associated screening failure for another personality disorder (Impulsive Personality Disorder) with treatment dropout for early childhood stuttering.